Communication Strategies in the Hospitality Industry: A Comparative Study of Lombok Astoria Hotel and Aruna Senggigi Resort - Azis, Ismail; Muhid, Abdul; Abdussamad, Zainudin (Universitas Pamulang, 2025)
This study examines the comparison of communication politeness strategies in the hospitality industry, specifically in hotels. Data were collected from two different hotels, Lombok Astoria Hotel and Aruna Senggigi Resort. The research method employed is qualitative descriptive, utilizing the Face Threatening Act (FTA) theory by Brown and Levinson (1987) as a foundational reference. Data collection involved observations, interviews, and recordings. The scope of this research focuses on the politeness strategies used by employees when interacting with customers, superiors, subordinates, and fellow employees in both hotels. The purpose of this study is to describe common occurrences and interactions in hotel environments, particularly in terms of how messages are expressed and responses are received. This insight aims to provide both theoretical and practical learning for students preparing to enter the hotel sector. The study analyzes and explains the factors influencing the expressions used by employees when serving guests and collaborating with superiors, subordinates, and colleagues. Findings indicate that the use of politeness strategies at Lombok Astoria Hotel is predominantly characterized by Save-Face strategies, while Aruna Senggigi Resort employs both Save-Face and Face Threatening Act strategies. The factors contributing to the use of these politeness strategies include familiarity, time, and place, which are further supported by the context of the interactions and the messages conveyed during conversations.